Development of Acid-Base Teaching Materials Using the Four Step Teaching Material Development Method for Vocational Students in Agricultural Product Processing Agribusiness - Nurlatifah*, Nurlatifah; Anwar, Sjaeful; Rohman, Ijang; Sianturi, Winda Fourthelina; Pusfitasari, Dewi Vitama (Universitas Syiah Kuala, 2025)
Chemistry learning in vocational schools is often limited to general concepts and lacks connection with students vocational expertise, making it difficult for them to apply theory to practice in agricultural product processing. This study aims to develop acidbase teaching materials using the four-step teaching material development (4STMD) method for students in the agricultural product processing agribusiness program at vocational high schools. The research responds to the lack of curriculum-aligned and contextually relevant resources that integrate chemistry with vocational practices. The study employed development research (DR), focusing on the first two stages of the 4STMD method: selection and structuring. In the selection stage, materials were designed based on basic competencies 3.5 and 4.5, producing eight learning indicators and sixteen concept labels. Acidbase concepts were compiled from national and international textbooks and contextualized with agricultural applications, such as pH control in fermentation. In the structuring stage, concept maps, macro structures, and three levels of representation (macroscopic, microscopic, and symbolic) were developed to link chemical theory with agricultural practices. The draft materials were refined through expert review to ensure clarity and scientific accuracy. The results indicate that the developed teaching materials are systematic, scientifically valid, and relevant to the curriculum. They also integrate substantive and pedagogical contexts that support students vocational learning needs. This study shows that the 4STMD method is effective for producing chemistry teaching materials that are structured, contextual, and applicable, thereby enhancing the relevance and quality of chemistry education in vocational high schools